Prefrontal sonic treatment: MR findings. - Kahn, L; Heiserman, J E; Hodak, J A; Foster, C A (American Journal of Neuroradiology, 1992)
The authors describe the use of MR in a patient who underwent prefrontal sonic treatment for relief of intractable headaches. MR demonstrated well-demarcated regions of encephalomalacia within the white matter of the frontal lobe (with relative sparing of cortex) in a characteristic conical volume that corresponded to the insonified regions.